Exploring teachers' perceptions of STEAM teaching through professional development: implications for teacher educators. Issue 3 (27th May 2017) - Herro, Danielle; Quigley, Cassie
Abstract : This research involves a multi-year study examining the perspectives and classroom practices of 21 middle school mathematics and science teachers, in the southeastern United States, participating in professional development (PD) exploring science, technology, engineering, art and mathematics (STEAM) literacies. This study sought to understand teachers' perceptions and practices before and after a PD in which STEAM integration was explored through project-based learning involving the political, social, economical, environmental and historical context of a local river. Participants used digital media as a means of communicating and collaborating with peers and mentors, collecting and analyzing data, and creating and sharing projects. Results suggest teachers increased their understanding of STEAM to teach content and perceived the STEAM PD as an effective initial step to change practice, citing the importance of collaboration and technology integrated directly into the learning process. Implications from this study offer other teacher educators valuable considerations towards developing successful STEAM PD to effect successful STEAM teaching.